MORFOLOGI DAN ANATOMI Chrysanthemum morifolium Ramat. var. puspita nusantara dan var. tirta ayunisertaChrysanthemum indicum L.var. mustika kaniya - Isvana Dalaila; Kusrinah Kusrinah; Lianah Lianah (Al-Hayat: Journal of Biology and Applied Biology, 2019)
Chrysanthemum including ornamental plant commodities are much-loved community. Chrysanthemum has a high economic value and potential to be developed. The diversity of morphological and anatomical characters is not currently widely practiced. This study aims to determine the morphological and anatomical characteristics of C. morifolium Ramat. var. puspitanusantara, and var. tirtaayuni and C. indicum L. var. mustikakaniya. Sampling by purposive random. The study was conducted in May - June 2017 in Kenteng Village, Bandungan District, Semarang District. The results showed that the results showed that C. morifolium Ramat var. puspitanusantara and var. tirtaayuni and C. indicum L. var. mustikakaniya have variations of morphology, especially on leaves and flowers, variations in leaf organ form, and base. Variations of flowering organs include the number of flowers per stem, the number of ribbon flowers, and the freshness of the flower. Anatomical characters based on tissue arrangement of stem and leaf organs have similarities.